The 2023 Bethesda System for Reporting Thyroid Cytopathology: A review update - A. Parmar Riddhi; Patel Keval (Journal of Clinical and Scientific Research)
The Bethesda System for Reporting Thyroid Cytopathology is the first reporting system in non-gynaecologic cytopathology after the Bethesda system for Reporting Cervical Cytopathology. It provides a uniform reporting system for pathologists and clinicians in thyroid cytology. The system has six diagnostic categories with defined criteria, risk of malignancy (ROM) and management recommendations. It underwent two revisions in 2010 and 2017, and a third edition was published in 2023. This review summarises the system, including potential pitfalls and molecular testing. Each category has an updated ROM and an average with a range of cancer risk. The atypia of undetermined significance sub-categorisation is simplified into two groups based on ROM and molecular profiling. Paediatric thyroid disease and its ROM along with management algorithms are discussed. The nomenclature aligns with the 2022 World Health Organization Classification of Thyroid Neoplasms. Two new chapters cover the use of molecular, ancillary testing in thyroid cytopathology with clinical perspectives and imaging findings in thyroid disease.